Electrodeposition of spinel MnCo2O4 nanosheets for supercapacitor applications. (21st October 2015) - Sahoo, Surjit; Naik, Kusha Kumar; Rout, Chandra Sekhar
Abstract: Herein, we report a facile, low-cost and one-step electrodeposition approach for the synthesis MnCo2 O4 (MCO) nanosheet arrays on indium doped tin oxide (ITO) coated glass substrates. The crystalline phase and morphology of the materials are studied by x-ray diffraction, energy dispersive x-ray analysis and field-emission scanning electron microscopy. The supercapacitor performance of the MCO nanosheets are studied in a three-electrode configuration in 2 M KOH electrolyte. The as-prepared binder-free electrode shows a high specific capacitance of 290 F g −1 at 1 mV s −1 with excellent cyclic stability even after 1000 charge/discharge cycles. The obtained energy density and power density of the MCO nanosheets are 10.04 Wh kg −1 and 5.2 kW kg −1 respectively. The superior electrochemical performances are mainly attributed to its nanosheet like structure which provides a large reaction surface area, and fast ion and electron transfer rate.